Refractive trends in 15-year-old adolescents at optometric practices in southern Sweden between 2007 and 2020 - Bro, Tomas; Brautaset, Rune (Scandinavian Journal of Optometry and Visual Science, 2023)
The purpose of this study was to analyse the distribution of refractive errors in 15-year-old adolescents at optometric practices in southern Sweden between 2007 and 2020. Refractive data were collected retrospectively from clinical records in five optometric practices in southern Sweden. The inclusion criteria were individuals visiting the practice at an age of 15 years between 2007 and 2020. The refractive errors were classified by the spherical equivalent (SE) (sphere + 1⁄2 cylinder) as follows: myopia (SE ≤ -0.5 D), hyperopia (SE ≥ 0.5 D), emmetropia (-0.5 > SE < 0.5 D). The astigmatism axis (-1.5 DC) was analysed as with-the-rule, against-the-rule and oblique according to traditional methods. To examine trends, the average refraction and distribution of refractive errors were compared between two selected time periods, 2007–2013 and 2014–2020. During the time frame 500 adolescents aged 15 years were examined in the selected optometric practices. Myopia was found in 34%, emmetropia in 35% and hyperopia in 31%. Among 37 individuals with astigmatism, the most common axis was with- the-rule (41%), followed by oblique (32%) and against-the-rule (27%). No significant differences could be found in the distribution of different refractive errors between the periods 2007–2013 and 2014–2020. Nor could any significant difference in average refraction be found. In contrast to the expected global rise in myopia as predicted by WHO and the high prevalence of myopia reported in some parts of the world, we could not find convincing changes in distribution between myopia and hyperopia in this cohort of Swedish adolescents.